Studi Pengaruh Titik Penambahan Sodium Isobutyl Xanthate (SIBX) dan Kecepatan Impeller pada Performa Flotasi Mineral Tembaga - Oktikawati, Anjar; Nugraha, Cahyo Ady; Soedarsono, Johny Wahyuadi (Rekayasa Material, Manufaktur dan Energi, 2023)
Evaluation of the use of the SIBX addition point and energy consumption in a flotation machine is an optimization effort to increase recovery in a valuable mineral separation process. The purpose of this study was to maximize the use of reagents and energy consumption in flotation machines by looking for the effect of the SIBX addition point and impeller speed variations on copper recovery. In the experiments, the authors vary the impeller speed and the SIBX addition points. The impeller speed is varied into five different speeds. While the SIBX addition point into four different points. From the variation of the experiment, the test must be done within 20 flotation kinetics. Those tests were performed for 8 minutes and will generate 4 concentrates and tailings. From this information, a graph of the relationship between recovery and time is obtained, and it can be seen that the point of adding SIBX and impeller speed is to produce optimal recovery values. From the available tailings and feed, an analysis of particle size and distribution is also carried out to check the effectiveness of changing the impeller speed pattern to provide kinetic energy for particles of various sizes to collide with air bubbles and increase the probability of collection of valuable minerals, so that high recovery is obtained in various areas. particle size. Of all the speed variations used in the impeller, the best kinetic recovery comes from the addition of SBX in the 0 min, 2 min, and 4 min. While the worst comes from the addition in the 6 min. Copper kinetic recovery is only affected by the nature and amount of hydrophobic particles but is not affected by impeller speed. Copper recovery at each end of the experiment showed the same value which is an average of about 94%.